The Performance Analysis of Jalan Tengku Sulung in Botania, Batam Indonesia - Natasya Aurum Maharani; Andri Irfan Rifai; Joewono Prasetijo (Indonesian Journal of Multidisciplinary Science, 2022)
Jalan Tengku Sulung in Botania is a secondary collector road with traffic density. The dense population causes the traffic density on Jalan Tengku Sulung in Botania in Botania, damage to road access, and parking activities on the road. For this reason, a study was conducted to analyze the level of road performance on Jalan Tengku Sulung in Botania. The method used in this study is a survey and data analysis method using IHCM 1997. The data used in this study is the primary data in the form of location conditions, road dimensions, number and speed of vehicles. Secondary Data is required in the form of map location, population data, and land use. Based on the analysis that has been done, the degree of saturation at the intersection is 1.43 with LOS F. In contrast, the results of road performance analysis obtained the highest volume of vehicles occurred at 06:45-07: 00 with a total of 600,6 pcu/hour. Saturation degree value 0.92 with LOS E.